Facile and scalable synthesis of Fe-based metal organic frameworks for highly efficient photo-Fenton degradation of organic contaminants. (10th November 2022) - Wu, Qiangshun; Siddique, Muhammad Saboor; Yang, Yuankun; Wu, Mi; Kang, Li; Yang, Hanpei
Abstract: Fe-based metal organic frameworks (Fe-MOFs) being a newly developed photo-Fenton catalyst, have gained ever-increasing attention for environmental remediation, but have been limited by high synthesis cost (high energy-consumption and low yield). In this work, economical and scalable synthesis of Fe-BDC1 (BDC denotes as terephthalic acid) was achieved via facile stirring under ambient condition, and its adsorptive, photocatalytic, Fenton-like and photo-Fenton performances were comprehensively explored against contaminants removal. In comparison, synthesized Fe-BDC2 with the common solvothermal method, the yield of Fe-BDC1 increased 3.4 times. Also, its adsorption capacity towards Rhodamine B (Rh. B) increased about 5.85 times. Moreover, the significantly improved degradation of Rh. B was observed in the Fenton-like and photo-Fenton systems with the increased reaction rate constants up to 4.90 and 2.33 times, respectively. This enhanced catalytic performance of Fe-BDC1 was mainly attributed to the enlarged specific surface area (SSA) and favorable electron separation and migration, resulting into the accelerated ≡Fe(II)/≡Fe(III) cycle and increased yield of reactive oxidative species (ROSs). Additionally, the unique light-induced adsorption enhancement further strengthened the contaminants removal. Fe-BDC1 as photo-Fenton catalyst was found superior over conventional catalysts in terms of advantages including: low dose requirement of catalysts (decrease in an order of magnitude) and H2 O2, wide pH working range (3.0–9.0), excellent reusability and stability, universal removal behavior against all organic pollutants, and remarkable synergism between photocatalysis and Fenton-like process with synergistic factor of 77.23%. Moreover, the Fe coordinative unsaturated sites (Fe CUSs) and ·OH were determined as the active sites and the main ROSs, respectively, responsible for highly efficient pollutant degradation. This work gives a feasible solution for the preparation of Fe-MOFs with low synthesis cost and high yield, paving ways for their practical mass application in heterogeneous photo-Fenton oxidation. Graphical abstract: Image 1 Highlights: Successfully synthesis of Fe-MOFs with low cost and high yield. Significantly enhanced adsorption, Fenton-like and photo-Fenton performances were acquired. Visible light induced adsorption enhancement further strengthen contaminates removal. The synergism between photocatalytic and Fenton-like process was demonstrated. Favorable electron separation and migration accelerated ≡Fe(II)/≡Fe(III) cycle.